Family Resilience, Support, and Functionality in Breast Cancer Patients: A Longitudinal Pre- and Post-Operative Study - Dimitrios Charos; Maria Andriopoulou; Giannoula Kyrkou; Maria Kolliopoulou; Anna Deltsidou; Anastasia Bothou; Victoria Vivilaki (Behavioral Sciences, 2025)
This longitudinal study investigated changes in family resilience, support, and functionality among breast cancer patients during the pre-operative and post-operative phases. The study was grounded in McCubbin’s model, emphasizing the psychosocial impact of illness and the cultural dynamics of the Greek family system. A longitudinal cohort study was conducted on women diagnosed with breast cancer, aged over 18, undergoing mastectomy, fluent in Greek, and capable of completing questionnaires at two time points, pre- and post-operatively. Standardized instruments were used: the Family Assessment Device (FAD), the Family Crisis Oriented Personal Evaluation Scales (F-COPES), the Family Problem Solving Communication Scale (FPSC), and the Family Support Scale (FS-13). Data were analyzed using paired t-tests, ANOVA, and partial correlations. The sample consisted of 58 women with breast cancer. The mean age of participants was 52 years. According to post-operative measurements, the scales that had a significant change were FS-13 (change −12 and SD = 6.9, paired t-test, p < 0.001), and the subscale “Problem Solving” of FAD (change 0.13 and SD = 0.44, paired t-test, p = 0.048). The remaining scales did not change significantly post-operatively. Depending on the type of treatment, the scales that had a significant difference post-operatively regarded the participants, who had undergone chemotherapy in the dimension “Acquiring Social Support” (ANOVA = 0.173, p = 0.030), the participants, who had undergone radiotherapy in the dimension “Seeking spiritual support” (ANOVA = 0.122, p = 0.035), and in the FS-13 scale across all treatment types (ANOVA = 0.458, p < 0.001). The post-operative phase of breast cancer was a psychosocially vulnerable time, accompanied by an increase in family dysfunction and a significant decrease in family support across all types of treatments, while patients receiving chemotherapy or radiotherapy experienced a corresponding decrease in social and spiritual support. Finally, enhanced family support was associated with improved family resilience, highlighting the need for targeted psychosocial interventions during this period.